A more straightforward derivation of the LR for a database search. (January 2015) - Berger, Charles E.H.; Vergeer, Peter; Buckleton, John S.
Highlights: This paper provides a new simpler derivation of the LR for a DNA database search. The short and the conventional derivations of the LR are given for 4 scenarios. The shorter derivations are easier to follow and help understanding the problem. Abstract: Matching DNA profiles of an accused person and a crime scene trace are one of the most common forms of forensic evidence. A number of years ago the so-called 'DNA controversy' was concerned with how to quantify the value of such evidence. Given its importance, the lack of understanding of such a basic issue was quite surprising and concerning. Deriving the equation for the likelihood ratio of a DNA database match in a much more direct and simple way is the topic of this paper. As it is much easier to follow it is hoped that this derivation will contribute to the understanding.